ULTRASOUND-GUIDED BRACHIAL PLEXUS NERVE BLOCK IN DONKEYS - Ayman S Atiba; Alaa Ghazy; Foad A Farrag; Mohammed Abu El-Magd; Essam A Almadaly (Slovenian Veterinary Research, 2019)
This study was conducted to describe and evaluate the ultrasound-guided technique and the anatomical relation for brachial plexus block in donkeys. In the first study, three donkey's cadavers were used to determine the neuroanatomical description of the brachial plexus. In the second study, four donkeys were used to evaluate the ultrasound structure of brachial plexus and the distribution of methylene blue solution that was injected around the nerves during subsequent postmortem anatomical dissection. In the third study, six donkeys were used to evaluate the efficient of the ultrasound-guided brachial plexus block after injection of lidocaine. Ultrasound was used to identify brachial plexus and blood vessels. Anatomical scrutiny assured the relationship between the nerves and the blood vessels. The nerves were adequately stained with methylene blue solution in all donkeys. A volume of 25 mL of lidocaine per injection site resulted in effective sensitive and motor block of forelimbs nerves after brachial plexus block. Based on the obtained data we could conclude that brachial plexus nerve block guided by ultrasound can be used in surgery of donkey distal fore limb.